Diagnóstico do setor administrativo de uma rede de postos de combustíveis - Limberger, Augusto Henrique Damiani (2022)
The present study aimed to analyze the control and management tools of a network of gas stations, in addition to identifying and suggesting opportunities for improvement that may contribute to the company's decision-making. The research methodology is qualitative, studying the controllership tools used in the company. Data collection was carried out through an interview with the administrative director and participant observation within the company. In the data collection, four large groups of controlling areas were evidenced, namely organizational administration, human resources, finance and costs, and sales and marketing. In the data collection, it was possible to observe that the company uses some control and management tools as a good system for management activities and operational activities, and also has a good diversity of already established result indicators. The report pointed out other opportunities for improvement in the management area, such as the preparation of a documented strategic plan, the documentation of employee training and also the need to have a person dedicated to calculating the company's margins. The results obtained through the analysis and diagnosis of the environment show that the company has even more potential to achieve its objectives, implementing controllership and strategic planning.